The mature athlete with hip arthritis (Clinics in Sports Medicine, 2011)
Degenerative arthritis of the hip is a common finding in the mature athlete and can have a significant impact on the quality of life of these patients. This chapter reviews the treatment modalities for early arthritis of the hip with a special focus on the current evidence for the role of hip arthroscopy in the care of these patients.